Crystal Structure and Magnetism of Fe1−xTe (x=0.31). Issue 23 (23rd September 2022) - Prots, Yurii; Clark, William P.; Schmidt, Marcus; Burkhardt, Ulrich; Rößler, Sahana; Fitch, Andy; Grin, Yuri; Schwarz, Ulrich
Abstract: Reaction of iron‐tellurium mixtures in the composition range from Fe0.41 Te0.59 to Fe0.43 Te0.57 followed by quenching to ambient temperature yields the high‐temperature δ phase Fe1− x Te (0.25< x <0.31). Single crystals of δ phase Fe1− x Te, with x =0.31(1), are obtained by reacting Fe−Te mixtures with nominal composition Fe0.43 Te0.57 in closed ampoules at 973 K for 15 days before quenching to ambient temperature. In accordance with the chemical transport behavior of other phases in the iron‐tellurium system, the refined composition of the single crystals Fe1− x Te with x =0.31(1) suggests that crystallization and growth preferably occur in the tellurium‐rich part of the homogeneity range.The resulting crystals adopt a monoclinic crystal structure with unit cell parameters a =6.645(2) Å, b =3.8409(6) Å, c =11.314(3) Å, β =90.47(1)°, Z =4 (space group I 2/ m, non‐standard setting of C 2/ m ). Single crystal structure refinement reveals a NiAs motif with partial occupation in every second iron layer along [001]. Magnetic susceptibility measurements indicate antiferromagnetic order below 400 K. Abstract :